Exploring Gender Differences in Coding at the Beginning of Primary School - Montuori, Chiara; Ronconi, Lucia; Vardanega, Tullio; Arfé, Barbara (Frontiers in Psychology, 2022)
The gender gap in Computer Science is widely documented worldwide. Only a few studies, however, have investigated whether and how gender differences manifest earlier in the learning of computing, at the beginning of primary school. Coding, seen as an element of Computational Thinking, has entered the curriculum of primary school education in several countries. As the early years of primary education happen before gender stereotypes are expected to be fully acquired, the opportunity to learn coding for boys and girls at that age might in principle help reduce the gender gap later observed in Computer Science education. Prior research findings however suggest that an advantage for boys in coding tasks may begin to emerge already since preschool or the early grades of primary education. In the present study we explored this hypothesis, examining whether the coding abilities of 1st graders, at their first experience with coding, are affected by gender differences, and if their presence associates with gender differences in executive functions (EF), in particular in response inhibition and planning skills. Earlier research has shown a strong association between children’s coding abilities and their EF, as well as the existence of gender differences in the maturation of response inhibition and planning skills, but with an advantage for girls. In this work we assessed the coding skills and EF (response inhibition and planning) skills of 109 Italian first graders, 45 girls and 64 boys, before an introductory coding course, when the children had no prior experience of it. We then repeated the assessment after the children had been exposed to learning of coding. The results show no statistically significant difference between girls and boys at the pretest. Yet, an advantage in coding emerges for boys at the posttest, without any differences appearing in EF between boys and girls. Mediational analyses show that the observed gender effects in coding are not mediated by children’s EF (response inhibition or planning abilities). Other factors must thus be accounted for to explain this phenomenon.